The relationship between proactive personality and migrant workers’ perception of technical unemployment risk under the impact of artificial intelligence in China - Xu, Guanglu; Xue, Ming (Frontiers in Psychology, 2025)
IntroductionUnder the background of rapid progress of artificial intelligence (AI) technology, migrant workers are at a high risk of becoming unemployed due to their low levels of human capital. As for the influencing factors of unemployment risk perception, individual characteristics are an important one. However, there remain few studies exploring the impact of personality on the perception of technical unemployment risk among migrant workers under the impact of AI. Therefore, this study examines the relationship between proactive personality and migrant workers’ perception of technical unemployment risk, focusing on the mediating roles of AI learning and AI self-efficacy.MethodsThis study collected data through the research platform “Credamo”. A total of 551 questionnaires were recovered in this survey, of which 446 valid questionnaires were reserved for research.ResultsThe research results show that: proactive personality was negatively correlated with migrant workers’ perception of technical unemployment risk; AI learning and AI self-efficacy mediated this relationship independently, and played a chain-mediating role in this relationship.DiscussionThe present study contributes the perception of technical unemployment risk literature by highlighting the impact of proactive personality and the chain mediating role of AI learning and AI self-efficacy in a sample of Chinese migrant workers. The empirical results of this paper are considered as helpful for organizations to formulate the policies aimed at alleviating migrant workers’ perception of technical unemployment risk under the impact of AI technology.